Identifikasi Kesalahan Pengerjaan Materi Dilatasi Waktu Berdasarkan Newman Error Analysis (NEA) - Napsawati, Napsawati; Yusdarina; Sakti, Irma; Idamayanti, Reski (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2023)
The purpose of this paper is to identify student errors in working on time dilation questions based on Newman Error Analysis (NEA). This research is a qualitative descriptive study. Data collection was carried out through a written test which contained 5 time dilation questions and a non-written test in the form of an interview. The results of this study indicate that the types of errors made by students are 20.0% understanding errors, 5.19% transformation errors, 26.67% skills process errors and 6.67% final answer writing errors. Meanwhile, based on the results of interviews with students, it shows that students' mistakes are caused by students' lack of understanding in interpreting time dilation questions, students are less thorough and in a hurry in working on questions and have not been able to use formulas correctly.